Robot Sociali per l’Assistenza: Inganni Pro-sociali ed Etica - Rossi, Silvia; Rossi, Alessandra; Esposito, Raffaella (Filosofia Morale/Moral Philosophy, 2025)
Social Assistive Robotics aims to improve people’s lives by providing assistance through interaction. There are settings where these robots need to encourage people to comply with instructions and advice, and also show empathetic reactions, which is a crucial aspect for achieving effective behaviour change. Such behaviors can be configured as deceptive. Deception is a complex behavior in human interactions and can compromise people’s trust. In this paper, we introduce different types of potentially deceptive behaviors that can be used in socially assistive robotics and discuss the ethical implications in human-robot interaction.